2004
DOI: 10.1159/000076744
|View full text |Cite
|
Sign up to set email alerts
|

Five Months of Physical Exercise in Hemodialysis Patients: Effects on Aerobic Capacity, Physical Function and Self-Rated Health

Abstract: Background: The number of chronic renal failure patients treated by hemodialysis (HD) is continuously increasing. Most patients have reduced physical capacity and have a high risk of cardiac and vascular diseases. The aim of this study was to determine the effects of 5 months physical exercise of HD patients’ physical capacity, self-rated health and risk factors for cardiovascular disease. Methods: 33 HD patients were included in the study. Inclusion criteria: HD for more than 3 months, age >18 years. Exclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 23 publications
2
101
0
2
Order By: Relevance
“…For example, coupling frequent dialysis with another intervention(s) (e.g., exercise) targeting these contributing physiologic mechanisms may lead to even greater improvements in physical function. We find it particularly interesting that the improvements in both the PHC score and PF score in the FHN trial were similar in magnitude to changes demonstrated previously with exercise interventions (16)(17)(18). There is also notable overlap in the physiologic mechanisms by which exercise and frequent hemodialysis may improve physical function.…”
supporting
confidence: 73%
“…For example, coupling frequent dialysis with another intervention(s) (e.g., exercise) targeting these contributing physiologic mechanisms may lead to even greater improvements in physical function. We find it particularly interesting that the improvements in both the PHC score and PF score in the FHN trial were similar in magnitude to changes demonstrated previously with exercise interventions (16)(17)(18). There is also notable overlap in the physiologic mechanisms by which exercise and frequent hemodialysis may improve physical function.…”
supporting
confidence: 73%
“…Being on dialysis requires a lot of time. Physical activity is probably not a first priority for these patients, and thus even exercise training before or after dialysis sessions have been quite unsuccessful [10]. Therefore, all reasons for not completing the program could be attributed directly and indirectly to the underlying illness.…”
Section: Discussionmentioning
confidence: 99%
“…RATIONALE: Physical activity levels are strikingly reduced in patients on dialysis (9). There is overwhelming evidence from observational studies that regular exercise improves physical functioning, exercise capacity, and physical performance and has a favourable influence on metabolic profiles (10)(11). Exercise includes cardiovascular and resistance training, and yoga in various combinations.…”
Section: No 4 Part I -Management Of Various Cardiovascular Complicmentioning
confidence: 99%